Age factor and COVID-19 potential ethical and unethical issues - Santiago Herrero (World Nutrition Journal, 2020)
The presentation of ethical guidelines by various scientific societies during the scenario of the COVID-19 pandemic in Spain is surprising when evidencing proposals for treatment and support due to "age ranges" that could be ethically unfair or at least not clearly understandable for the older group, unlike other guides such as the American and European Society for Critical Care and Intensive Medicine. Terms such as distributive justice, prioritization without paternalistic interference, introduction of strategies that maximize survival to hospital discharge, and the number of years of life saved are discussed during the presentation.The aim of this presentation is to clarify different ethical aspects about the elderly patients in the time of being admitted in the ICU during COVID-19 scenario.